(3eJf QSGdI GHf RjOhfs - (3GHf RjOhf , CHh GdhdjO CMeO Hf YHO Gddg Hf ZGdH Hf RjOhf GdeNRhej GdCfOdSj, CHh GdhdjO,J (B463 (3g` s
(3ChdgG (B:s
(3CeG HYO CjgG GdeUGH HYbdg GdeaQW HLgdg GdHjf SbWg GdaGMT ZdWg GdYGTQ ai Pjd EZJQGQg s
(3BNQgG (B:s
(3Vef LgdJ faSg bOQg QCi ZjQg efgeG dG jQi gPG GdHjJ ef TYQ GdeJfHi NJeJ HPcQg GdQSGdI defGSHI eG bHdg bO JeJ gPg GdQSGdI GdeYQhaI HQSGdI CHh GdhjO Hf RjOhf s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B27s
(3GdfSNI HgG MhGTs
(3HgG Jedc HGSe YHO dGdg Hf YHO GdhGMO Hf YHO GddWja Hf TYjH Hf YHO dGSdGe hjQLY JGQjNgG Edi SfI (B1294 (3g`s
(3HgG fXGe GdJYbjHIs
(3HChdg hBNQg ahGFO s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B1 - (3U (B158 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B1 - (3U (B284s
Keywords: (3GdeLGejYs